Study on the Formation of Secondary Organic Aerosol by Ozonolysis of Citral in the Atmosphere - Chenxi Zhang; Xuesong Cao; Xiaomin Sun; Hengjun Peng (Aerosol and Air Quality Research)
Abstract A major research area in atmospheric chemistry focuses on the formation of secondary organic aerosol (SOA), which contains a large variety of low-volatility organic compounds when generated by the ozonolysis of monoterpenes. Thus, we apply quantum chemistry and kinetic calculations to investigate the ozonolysis of citral, which begins with the formation of primary ozonides (POZs) that decompose into Criegee intermediates (CIs). Although CIs have been previously implicated in tropospheric oxidation, the majority are simple compounds for their class, such as CH2OO• or CH3CHOO•. This study, however, reports on the generation and reaction kinetics of larger CIs, which have been shown to oxidize NO and SO2 into NO2 and SO3, respectively, leading to the production of nitric acid and sulfuric acid. Furthermore, the reactions between these CIs, and H2O and SO2 may serve as the dominant mechanism for removing the former from the troposphere, thereby determining the atmospheric CI concentrations. The low-volatility organic compounds potentially arising from the ozonolysis of citral, including aldehydes (—C(=O)H), ketones (—C(=O)—), alcohols (—OH), and hydroperoxides (—OOH), can form SOA through the nucleation, condensation, and/or partitioning of the condensed and gaseous phases.